Penerapan Metode Alternatif Pada Permainan Kartu Capsa Banting - Albertus Josef Andika; Djoni Haryadi Setiabudi; Lily Puspa Dewi (Jurnal Infra, 2019)
Card games in Indonesia have many types that are often played starting from minum-minuman, hantu-hantuan, tepok nyamuk, 24, 41, and many more. Capsa is also part of the card game. Many studies have tried to apply various algorithms to the card game as a decision maker, but from some similar studies, no one has ever tried to apply other algorithms to the Capsa game and provided satisfaction to players who played without the algorithm or with other algorithms. So in this paper we will apply alternative algorithms inspired by Genetic Algorithm into the Capsa game. Application of Alternative Algorithms in the program is found in 3 main functions of AI in the game, namely tigaWajik, aiPlay, and startCombo where the final result of the algorithm is a combo card that will be released by the enemy replacing the usual algorithm method. The game is made with 2 modes, namely without Alternative Algorithm and with Alternative Algorithm. Players can choose the desired mode before starting the game. Testing is done by asking prospective respondents to try the game and fill out the player satisfaction questionnaire. From the results of the questionnaire conducted, the game that was made successfully gave a sense of satisfaction to the players who played. Various positive responses and other creative ideas emerged for the development of the program.